2003
DOI: 10.1038/nmat966
|View full text |Cite
|
Sign up to set email alerts
|

Nanophase separation and hindered glass transition in side-chain polymers

Abstract: Nanophase separation on length scales of 1-5 nanometres has been reported previously for small-molecule liquids, metallic glasses and also for several semicrystalline, liquid-crystalline and amorphous polymers. Here we show that nanophase separation of incompatible main and side-chain parts is a general phenomenon in amorphous side-chain polymers with long alkyl groups. We conclude from X-ray scattering and relaxation spectroscopy data for higher poly(n-alkyl acrylates) (PnAA) and poly(n-alkyl methacrylates) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

57
400
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(457 citation statements)
references
References 33 publications
57
400
0
Order By: Relevance
“…From those experiments, the existence of two different glass-transitions was proposed: one associated to the freezing of the motions within the alkyl nanodomains and the other with that of the main-chain dynamics. 81,84,88 Using a selective technique providing space/time resolution at a molecular level like NS combined with isotopic labeling was thus essential to check the validity of such scenario. This was realized in recent works on PnMAs with different number of carbons in the alkyl side-group n C .…”
Section: Polymers With Complex Monomeric Units Or/and Chain Architectmentioning
confidence: 99%
“…From those experiments, the existence of two different glass-transitions was proposed: one associated to the freezing of the motions within the alkyl nanodomains and the other with that of the main-chain dynamics. 81,84,88 Using a selective technique providing space/time resolution at a molecular level like NS combined with isotopic labeling was thus essential to check the validity of such scenario. This was realized in recent works on PnMAs with different number of carbons in the alkyl side-group n C .…”
Section: Polymers With Complex Monomeric Units Or/and Chain Architectmentioning
confidence: 99%
“…This peak is roughly in the same position as the "prepeak" in the x-ray pattern, reinforcing the idea that in polymers with bulky side groups such a "prepeak" is representative of the polymer backbone distance. 11,12,14,50,51 This average distance could be estimated from the peak position as 2π/0.6 Å −1 = 10.5 Å. S MC/MC (Q) smoothly decreases toward higher Q but still shows a small shoulder around 1.2 Å −1 , i.e., around the "main" peak.…”
Section: A Atomistic Approach 1 Short-range Order In Pvpmentioning
confidence: 99%
“…[1][2][3] Moreover, it has been shown that increasing the size of side groups has a deep impact on the structure and dynamics of polymers. Of particular interest is the family of poly(nalkyl-methacrylates), 2,[4][5][6][7][8][9][10][11][12] where x-ray and neutron diffraction analysis show that nanosegregation occurs between backbone and side groups. The effects of these nanosegregated domains on the local dynamics remain however unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Relative to the alpha relaxation, the beta relaxations become slower and more VFT-like with increasing alkyl side-chain length, a trend which is reminiscent of that observed in the poly(n-alkylacrylate) sidechain polymers. 29 The transition from Arrhenius to VFT like temperature dependence indicates that the secondary relaxations of these ILs become more cooperative in nature with increasing alkyl side-chain length 30 and provides a dynamical signature of the phase separated liquid morphology in these ILs. 29 The 2 ] are approximately 30 and 300 times slower, respectively, than the corresponding alpha relaxation process and have nominally identical temperature dependences (Fig.…”
mentioning
confidence: 99%